A personal leadership statement (2023)
Prior to anything else, it's important to note that leadership and empowerment are topics that have recently received attention from the community at large as well as from instructors and students. In order to properly include leadership and empowerment into education, both individually and collectively, we first define these terms. This personal leadership statement emphasizes the skills and resources required to be an effective leader. Additionally, it is founded on earlier studies that have shown how effective leadership is in diverse areas of human engagement. Finally, our direct implication in leadership and empowerment which enables us to be a catalyst for positive change in not only our followers but also everyone around us.